9(2y-8)-(2y+2)=

Simple and best practice solution for 9(2y-8)-(2y+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(2y-8)-(2y+2)= equation:


Simplifying
9(2y + -8) + -1(2y + 2) = 0

Reorder the terms:
9(-8 + 2y) + -1(2y + 2) = 0
(-8 * 9 + 2y * 9) + -1(2y + 2) = 0
(-72 + 18y) + -1(2y + 2) = 0

Reorder the terms:
-72 + 18y + -1(2 + 2y) = 0
-72 + 18y + (2 * -1 + 2y * -1) = 0
-72 + 18y + (-2 + -2y) = 0

Reorder the terms:
-72 + -2 + 18y + -2y = 0

Combine like terms: -72 + -2 = -74
-74 + 18y + -2y = 0

Combine like terms: 18y + -2y = 16y
-74 + 16y = 0

Solving
-74 + 16y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '74' to each side of the equation.
-74 + 74 + 16y = 0 + 74

Combine like terms: -74 + 74 = 0
0 + 16y = 0 + 74
16y = 0 + 74

Combine like terms: 0 + 74 = 74
16y = 74

Divide each side by '16'.
y = 4.625

Simplifying
y = 4.625

See similar equations:

| f(x+6)=x^2+9x-1 | | (176-y)=(115+x) | | 5n-n+5=13 | | 4x^2+y^2+2y=0 | | -3=m-3 | | 3=l-5 | | 4n-2n+10=22 | | -9+y=7 | | f(x)=x^2+9x-1 | | 1.05t+0.63=-0.07t | | 4x+2(8)=4x(9) | | 10n+2=22 | | 13-6b=3+11b | | 9n+18=36 | | (99+x)=(176+y) | | -9(x+3)+3x+6=5x+9 | | 6.75t+7=15.5t+14 | | 4568b-4=7 | | -v+2=3 | | 116=-4(-4y)-9(2y)+y | | (w*3-9)+(w+4)=(w*3-9)+(w+4) | | 2x+3y=5.13 | | 16+b^2+6b=0 | | 4y^6(y^2+9y+2)= | | 8n^2-3n-16=24 | | -10+3x=-4 | | X+y=y+x+200 | | 57=3v+3 | | 89-116=-4(-4y)-9(2y) | | 4x+6+6x=36 | | x+y+z=2000zxy | | (7x-4x)=y |

Equations solver categories